PENYESUAIAN DIRI TERHADAP FENOMENA GEGAR BUDAYA DI LINGKUNGAN KERJA - Pratiwi, Ellya; Susanto, Yanti Oktavianti (Universitas Prof. Dr. Moestopo (Beragama), 2020)
The phenomenon of cultural shock in the work environment is an obstacle for immigrant employees both in their working performance and interpersonal communication in work environment. Therefore, adjustments are needed in order to adapt and communicate effectively. This research aims to determine the form of cultural shock in the work environment experienced by informants and how their efforts to adapt themselves to the culture shock phenomenon. Based on Lysgaard's U-curve model, the adjustment stage for a culture shock consists of the honeymoon, crisis, recovery and adjustment stages. This research used qualitative methods, with a phenomenological approach. The research found that there were two categories of cultural shock forms experienced by the informants. First, cultural shock on environmental differences, consisting of language, food, and weather. Second, cultural shocks in social life which consist of discriminatory attitudes due to ethnic and cultural differences, stereotypes, and discomfort with the communication climate in the company. Adaptation efforts were made, namely increasing intense interaction, learning Sundanese, understanding the character and habits of local employees, and participating in activities outside the company. The results of these adjustments depend on the intercultural communication competence and the character of each individual.